Ian Macdonald. (7th April 2009) - Keen, Harry
Abstract : Former professor of physiology Guy's Hospital Medical School, London (b 1921; q Guy's Hospital 1944; DObstRCOG, PhD, MD, DSc, FIBiol), died from an acute respiratory infection on 23 December 2008.